Some reflections on the model for the recognition by courts of civil law cases in agricultural law - Mucha, Joanna (Przegląd Prawa Rolnego, 2022)
The aim of the considerations – in the absence in the Code of Civil Procedure of a unified regulation devoted to the recognition by courts of cases in agricultural law – is to determine whether, in the light of the current legislation as well as the established views of the doctrine, there are premises for the separation of the procedural model of handling this type of cases. Two not mutually exclusive options are analysed: the admissibility of instituting separate proceedings in agricultural law cases, and recognition of such cases by specialised jurisdiction. In conclusion it is assumed that due to the difficulty of implementing the essential criterion for the qualification of cases to separate proceedings pertaining to their specificity rather than the proper jurisdictions of the entities involved, the first concept should be rejected. Moreover, this concept cannot be supported by any historical reasons. A more realistic solution seems to be based on the creation of specialised divisions or panels of judges adjudicating within the functioning structure of the judiciary.